Analisis Ketercapaian Indikator Habits of Mind (HoM) Siswa SMA - Hutajulu, Mastha; Wahyudin, Wahyudin (Jurnal Padegogik, 2020)
This study aims to analyze the achievement of each indicators habits of mind (HoM) senior high school students. The research method used is descriptive. The population in this study were high school students in the city of Bandung. The sample was chosen by 1 class consisting of 31 students. The instrument used was the Habits of Mind questionnaire. The results showed that the habits of mind of senior high school students were positive for the 12 indicators (75 %) and negatif for 4 indicators (25 %). This study can be recommended to improve the habits of mind (HoM) senior high school students.